Gambaran Faktor Eksternal sebagai Hambatan dalam Pengambilan Obat pada Penderita Kusta di Wilayah Kerja Puskesmas Sikumana Kota Kupang - Mikael M. Reca; Serlie K. A. Littik; Amelya B. Sir (Media Kesehatan Masyarakat, 2021)
Leprosy is a chronic infectious disease caused by leprosy germs (Mycobacterium leprae), which attack the skin and peripheral nerves. Treatment in leprosy patients needs to be done to break the chain of transmission and prevent defects. Routine taking of drugs is an important indicator in the efforts of treatment and support the patient to take medication until the completion of treatment. This study aims to the external barriers in drug-taking in leprosy patients at Sikumana Primary Health Center in Kupang. This was a qualitative research with the phenomenological approach. There were nine informants in this study consisting of the Multibacillary (MB) leprosy patiens, their families, public figures, and health workers. The data was obtained by interviews and observations. Furthermore, the data analysis was conducted qualitatively. The results showed that the obstacles in getting the leprosy medicines were the access to the health facilities and COVID-19 pandemic. In addition, there were problems about negative peers influence and slow services in acquiring the medicines. The role of health agencies should be more proactive in fulfilling leprosy drugs during the COVID-19 pandemic by delivering drugs to leprosy sufferers.